2020
DOI: 10.1155/2020/9457670
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Clinical Course of Vitreomacular Traction

Abstract: Background. To analyze the optical coherence tomography (OCT) characteristics as well as the clinical and demographic features to investigate their possible role to the course of vitreomacular traction syndrome. Methods. The inclusion criteria were vitreomacular adhesion with traction causing distortion of the retinal architecture, with or without the presence of an epiretinal membrane, regardless of the size of the adhesion; age >18 years; follow-up of at least three months; and adequate quality OCT scan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
(8 reference statements)
1
3
0
Order By: Relevance
“…Interestingly, several clinical-based studies revealed that the occurrence of a VMT was significantly associated with elder age and the mean age of patients diagnosed with VMT is around 65-75 years (range 48-83 years), with a predominance of females. 7,[16][17][18] These findings confirm our results. VMT is a special stage of posterior vitreous detachment (PVD), and studies in healthy adults with otherwise normal eyes have shown that posterior vitreous detachment (PVD) occurs in around 50% at the ages 30-39 years, whereas complete PVD is observed in 50% or more of individuals more than aged 70 years.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, several clinical-based studies revealed that the occurrence of a VMT was significantly associated with elder age and the mean age of patients diagnosed with VMT is around 65-75 years (range 48-83 years), with a predominance of females. 7,[16][17][18] These findings confirm our results. VMT is a special stage of posterior vitreous detachment (PVD), and studies in healthy adults with otherwise normal eyes have shown that posterior vitreous detachment (PVD) occurs in around 50% at the ages 30-39 years, whereas complete PVD is observed in 50% or more of individuals more than aged 70 years.…”
Section: Discussionsupporting
confidence: 92%
“…Residual ME remains an obstacle to complete visual function recovery in terms of decreased CMT and improved BCVA. Preoperatively, ME, caused by persistent attachment of the vitreous and inflammation, plays the principal role in the decline in visual acuity [ 27 ]. Mechanical surgical intervention can aggravate ME by damaging the blood-retinal barrier and promoting inflammatory exudates and leukocyte responses in the macular region.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high rates of PCMO generally in the DM populations, it is fair to conclude pharmaceutical management is suboptimal, and future efforts should be directed towards de-DOI: 10.1159/000521053 veloping more evidence-based medical therapies. For patients with VMT and DM before undergoing cataract surgery, it may be beneficial to undergo a vitrectomy to reduce the chances of developing post-operative PCMO or delaying cataract surgery for spontaneous resolution of VMT which has been observed in 11% of cases within 15 months [46,47].…”
Section: Discussionmentioning
confidence: 99%